Investigating the associations between organophosphate flame retardants (OPFRs) and fine particles in paired indoor and outdoor air: A probabilistic prediction model for deriving OPFRs in indoor environments. (April 2023) - Lu, Quang-Oai; Jung, Chien-Cheng; Chao, How-Ran; Chen, Pei-Shih; Lee, Chia-Wei; Thi Phuong Tran, Quynh; Ciou, Jyun-Yi; Chang, Wei-Hsiang
Graphical abstract: Highlights: The indoor OPFRs level was higher than those in outdoor, contrasting with PM2.5. Indoor TCEP was significantly positively associated with indoor and outdoor PM2.5. Indoor TCEP, TDCIPP, and TBOEP in warm season were greater than them in cold season. Predictive model for indoor air OPFRs performed a high accuracy. Human activity and interior decorating materials could predict indoor air OPFRs. Abstract: Contaminants of emerging concern such as organophosphate flame retardants (OPFRs) are associated with atmospheric fine particles (PM2.5 ), which pose the greatest health risk in the world. However, few surveys have explored the interaction between PM2.5 and OPFRs in residential paired indoor/outdoor environments. 11 priority OPFRs and PM2.5 were investigated across 178 paired indoor and outdoor air samples taken from 89 children's households in southern Taiwan, across cold and warm seasons. This involved exploring their associations with building characteristics, interior materials, and human activities. We developed a probabilistic predictive model for indoor OPFRs based on the indoor/outdoor (I/O) ratio of contaminants and an air quality index. The significant associations of paired indoor/outdoor OPFRs and PM2.5 were explored. The indoor level of OPFRs was greater than that of outdoor households, contrasting with PM2.5 . The I/O OPFRs ratio was higher than 1 (except for TEHP, EHDPP, and TCP), which suggests that the sources of OPFRs were primarily emitted from indoors. Indoor TCEP was significantly positively associated with indoor and outdoor PM2.5 . The OPFR level detected in apartments was higher than in houses due to the greater decoration, furniture and electronic devices. However, this was not the case for PM2.5 . TCIPP was the dominant compound in paired indoor and outdoor air. The indoor OPFR predictive model obtained a high accuracy with an R 2 value of 0.87. The material used in mattresses, the use of purifiers and heaters, and the total material area were the main influencing factors for indoor OPFRs in households. These findings could provide important evidence of the interaction between paired indoor/outdoor OPFRs and PM2.5 and interior equipment in different building types. In addition, it could prevent the potential risks posed by indoor/outdoor air pollutants and eliminate OPFR emissions through the selection of better construction and building materials.